Polyamine metabolism and cancer prevention. (20th March 2007) - Saunders, F.R.; Wallace, H.M.
Abstract : Colorectal cancer is one of a number of cancers that may be amenable to prevention. The NSAIDs (non-steroidal anti-inflammatory drugs) have been shown to be effective chemopreventative agents in humans, but their mechanism of action is not clear. The polyamines are cellular polycations that are essential for cell growth and are overproduced in cancer cells. It is our hypothesis that inhibition of polyamine metabolism is an integral part of the mechanism of cancer prevention mediated by NSAIDs.